Analysis of alternative commercial vehicle road user charges - Dan Wei; Genevieve Giuliano; Kelly-Anne Moffa; Zakhary Mallett (Transportation Research Interdisciplinary Perspectives)
As fuel tax revenues decline from increased fuel efficiency and the transition to alternative fuels, governments are searching for new revenue sources to support the transportation system. User fees are among the most widely considered substitutes. They could increase both system efficiency and the equity of transportation taxes by more closely aligning prices with costs imposed. We conduct an analysis of mileage-based user charges (MBUC) for trucks in California. We explore the differences in MBUC relative to current state fuel and weight fees in terms of revenues generated, changes in cost sharing among truck classes and commodity categories, and implications to the State economy as well as households from different income groups. Revenue neutral scenarios have little economy-wide impacts, but shares of fees paid differ across vehicle classes. Increasing the charge to include pollution costs results in negative economic outcomes. Distributional impacts are negligible.